Evidencing the Role of Erythrocytic Apoptosis in Malarial Anemia - Totino, Paulo R. R.; Daniel-Ribeiro, Cláudio T.; Ferreira-da-Cruz, Maria de Fátima (Frontiers in Cellular and Infection Microbiology, 2016)
In the last decade it has become clear that, similarly to nucleated cells, enucleated red blood cells (RBCs) are susceptible to programmed apoptotic cell death. Erythrocytic apoptosis seems to play a role in physiological clearance of aged RBCs, but it may also be implicated in anemia of different etiological sources including drug therapy and infectious diseases. In malaria, severe anemia is a common complication leading to death of children and pregnant women living in malaria-endemic regions of Africa. The pathogenesis of malarial anemia is multifactorial and involves both ineffective production of RBCs by the bone marrow and premature elimination of non-parasitized RBCs, phenomena potentially associated with apoptosis. In the present overview, we discuss evidences associating erythrocytic apoptosis with the pathogenesis of severe malarial anemia, as well as with regulation of parasite clearance in malaria. Efforts to understand the role of erythrocytic apoptosis in malarial anemia can help to identify potential targets for therapeutic intervention based on apoptotic pathways and consequently, mitigate the harmful impact of malaria in global public health.